Intimate Tragedies: Body Politics and Narrative Interruptions in Contemporary Rewritings of Shakespeare’s Richard III - MONAH, Dana (Studia Universitatis Babeș-Bolyai Dramatica, 2023)
When they set Shakespeare’s Richard III into one night and eliminate most of the male characters, Italian actor and playwright Carmelo Bene’s Richard III or the Terrible Night of a Man of War (1977) and Flemish dramatist Peter Verhelst’s Richard III (2004) turn Richard’s story into an intimate, private tragedy. This article argues that, influenced by ideas and concepts developed by the theorists of the historical avant-gardes, both practitioners condense, fragment, atomise the story they borrow from Shakespeare, shifting the focus from the events themselves to the characters’ perception of the events, and foregrounding the image of the suffering or disabled body.